Indonesia-Australia Timor Gap Agreement: A Pseudo Political Victory or Territorial Contest Defeat - Rinardi, Haryono; Hasanah, Maulida Alfi; Sulistiyono, Singgih Tri (Diponegoro University, 2023)
This article focuses on the dynamics of Indonesia-Australia relations in the context of the Timor Gap Treaty. Political victory or defeat over territorial disputes is vital in bilateral relations between Indonesia and Australia. Historical methods were used to examine the problem, in which the data is extracted from primary sources, including news and articles in newspapers and magazines. Many factors determine the issue of neighbourly relations between two countries. The research results show that Indonesia’s political interests are a priority in resolving the Timor Gap conflict. Australia’s recognition of Indonesia’s sovereignty over East Timor is the primary consideration for the Indonesian Government in resolving disputes in the Timor Gap. This factor also causes Indonesia to recognize Australia’s maritime claims over areas that close to Indonesia.